Compendium of South African Environmental Legislation - Morné van der Linde (Pretoria University Law Press (PULP), 2006)
Compendium of South African Environmental Legislation Edited by Morné van der Linde 2006 ISBN: 0-9585097-2-7 Pages: 565 Print version: Available Electronic version: Free PDF available